2021
DOI: 10.1186/s13049-021-00912-3
|View full text |Cite
|
Sign up to set email alerts
|

Survivors of avalanche accidents: posttraumatic stress disorder symptoms and quality of life: a multicentre study

Abstract: Background As any traumatic event, avalanches could trigger psychological disorders on survivors. Our objectives were to determine the prevalence of post-traumatic stress disorder among avalanche survivors and to evaluate post-traumatic stress disorder risks factors as well as the impact on quality of life. Methods A multicentre study was conducted in victims included in the North Alpine Avalanche Registry from 2014 to 2018. Data were collected thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Relevant data also show that loneliness, irritability, irritability, fear, depression, anxiety, pessimism, despair, and other adverse psychological problems affected the quality of life of cancer patients with the disease and could cause a vicious cycle between adverse psychology and pathophysiology [21]. In addition, after the occurrence of posttraumatic stress disorder, patients may have flashbacks and recurrence of traumatic memories, avoidance, and hypervigilance, which affected their quality of life [22,23]. Enabling psychological nursing took the patient as the center, according to the real idea of the patients' heart, to take targeted psychological counseling, so that the patients have a healthy and positive psychology, so as to improve the quality of life [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant data also show that loneliness, irritability, irritability, fear, depression, anxiety, pessimism, despair, and other adverse psychological problems affected the quality of life of cancer patients with the disease and could cause a vicious cycle between adverse psychology and pathophysiology [21]. In addition, after the occurrence of posttraumatic stress disorder, patients may have flashbacks and recurrence of traumatic memories, avoidance, and hypervigilance, which affected their quality of life [22,23]. Enabling psychological nursing took the patient as the center, according to the real idea of the patients' heart, to take targeted psychological counseling, so that the patients have a healthy and positive psychology, so as to improve the quality of life [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Preventive measures and early diagnosis of post-traumatic stress disorder may reduce the psychological burden. 64,188 Avalanche rescuers are also at risk for long-lasting psychological effects. Formal psychological support may be beneficial.…”
Section: Post-traumatic Stress Disorder After Avalanche Burialmentioning
confidence: 99%
“…19,37,38,62,63 At least 1 h of avalanche burial is usually required to reach a core temperature <30°C, at which fatal arrythmias become more likely. 64 In human simulations of avalanche burials, hypercapnia caused a 70% increase in cooling rates. 37,61 Core temperature cooling rate increases during and after extrication from snow burial because of exposure to the air, removal from the insulation of snow, and vasodilation of the extremities if the victim stands or walks.…”
Section: Traumamentioning
confidence: 99%
“…Hypoxia is a factor in ptsD allowing memory loss of a traumatic event in ptsD patients [72]. Post-avalanche survivors develop ptsD in approximately 11% of cases and it is presumable, but not demonstrated, that suffering hypoxia is a factor in this development [73]. Most studies investigating hypoxia in ptsD were animal studies; the directionality of hypoxia in ptsD has not been demonstrated and no study has investigated radiological signs of hypoxia in ptsD patients.…”
Section: Discussionmentioning
confidence: 99%